COLLECTIVE IDENTITY AND DIGITAL ACTIVISM IN FOOD WASTE GOVERNANCE: INSIGHTS FROM THE RUANG PANGAN COMMUNITY - Dodi Faedlulloh; Kholifatul Munawaroh; Yustina Yustina (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Food waste has become an increasingly urgent global issue, spurring the rise of community-based ecological initiatives, particularly those driven by youth. In Lampung Province, the Ruang Pangan Community has emerged as a key actor in the social food movement, combining surplus food redistribution, public education, and policy advocacy through a multi-level approach. This study explores the dynamics of the Ruang Pangan movement using New Social Movement (NSM) theory, with a focus on collective identity formation and digital activism in the context of food waste governance. Employing a qualitative methodology, data were gathered through in-depth interviews, participant observation, and document analysis. The findings reveal that Ruang Pangan seeks to build a collective identity under the label Food Heroes, broaden participation via digital platforms, and foster cross-sector collaboration within the local food ecosystem. However, the movement remains largely rooted in volunteerism, resulting in an internally focused collective identity that has yet to be fully expressed in the public sphere. Volunteer engagement is primarily motivated by personal moral concerns or social networking goals, rather than political awareness of structural inequalities in the food system. Furthermore, the movement faces critical challenges, including limited funding, institutional inertia, and low levels of broader public engagement. This study contributes to the theoretical discourse on contemporary social movements by highlighting the interplay between moral action and structural critique. It also offers practical insights for developing more inclusive and participatory food waste management strategies at the local level.